Educational Quality Management In Building Branding - Cici Rasmanah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
This study is motivated by the importance of quality management in strengthening the competitiveness of schools, particularly vocational institutions that face intense competition. The purpose of this research is to analyze the implementation of educational quality management and its relation to school branding at SMK Nurul Huda Al Gina Cimerak, Pangandaran. The research employed a qualitative approach with a case study design, using observation, interviews, and documentation as data collection techniques. Data were analyzed through Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that quality management was implemented through integrated planning, organizing, implementing, and controlling, which contributed to the improvement of teaching processes and student competencies. These quality outcomes serve as the main asset in strengthening school branding, particularly through the achievements of alumni in both employment and entrepreneurship. However, the branding strategy remains limited to simple promotional activities and lacks systematic communication, thereby reducing its effectiveness in enhancing the school’s image. It is concluded that educational quality functions as the fundamental basis for building public trust, while branding serves as a strategic instrument for reinforcing the image and competitiveness of the school.